Pros And Cons Of Artificial Intelligence (Ai) Technology By Local Guide In Dusun Adat Sade Rembitan Village In Central Lombok - NTB - Indonesia - Rizwan Hadi; Sri Wahyuni; M. Ilham H (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2024)
Technology is rapidly advancing today, with the most popular technology known as Artificial Intelligence (AI). This technological innovation greatly benefits the tourism sector. However, the implementation of Artificial Intelligence (AI) technology often sparks debate, including in the tourism industry. This study aims to identify the pros and cons related to the presence and use of AI technology by local guides at tourist sites that still maintain the authenticity of culture, such as in the Dusun Adat Sade, Rambitan Village, Central Lombok, West Nusa Tenggara, Indonesia. The research was conducted using an inductive approach, with a qualitative methodology, a case study research strategy, and a cross-sectional research time frame. Data collection and analysis were performed using data reduction, data display, and conclusion drawing. Data analysis utilized content analysis, categorizing data into specific themes or categories. Triangulation of methods and sources was employed for data validity. Methodological triangulation involved three methods: observation, interviews, and documentation. Additionally, source triangulation was conducted by interviewing 8 informants. The research findings categorized data into the following: Pros and Contras regarding Artificial Intelligence (AI) technology. After analyzing and processing the data from both categories, the majority of local guides in the Sade Traditional Village, Rembitan Village, exhibit a predominantly contra or skeptical attitude towards Artificial Intelligence (AI) technology due to concerns about Artificial Intelligence (AI) taking over their jobs. However, they still acknowledge technological advancements that facilitate their service to tourists. To further assess the extent to which Artificial Intelligence (AI) technology assists local guides, especially at tourist sites, further research on the benefits of Artificial Intelligence (AI) for supporting and facilitating local guides in their work is needed